2001
DOI: 10.1083/jcb.153.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Abp1, a Signal-Responsive F-Actin–Binding Protein, Links the Actin Cytoskeleton to Endocytosis via the Gtpase Dynamin

Abstract: The actin cytoskeleton has been implicated in endocytosis, yet few molecular links to the endocytic machinery have been established. Here we show that the mammalian F-actin–binding protein Abp1 (SH3P7/HIP-55) can functionally link the actin cytoskeleton to dynamin, a GTPase that functions in endocytosis. Abp1 binds directly to dynamin in vitro through its SH3 domain. Coimmunoprecipitation and colocalization studies demonstrated the in vivo relevance of this interaction. In neurons, mammalian Abp1 and dynamin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
260
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(267 citation statements)
references
References 54 publications
6
260
1
Order By: Relevance
“…On the basis of the intracellular localization of DBN-1 and on a tentative functional comparison with its relatives, DBN-1 could furthermore modulate the plasticity and function of postsynaptic sites of neuromuscular junctions, analogous to mAbp1 and drebrin, which are known as essential players in both neurological [43][44][45]28 and immunological 30,29 synapses. In addition, DBN-1 may be involved in vesicle transport, similar to yeast and mammalian Abp1 homologues, which are well-described key regulators of receptor-mediated endocytosis, vesicle trafficking and endocytic structure disassembly [46][47][48][49]32 .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the intracellular localization of DBN-1 and on a tentative functional comparison with its relatives, DBN-1 could furthermore modulate the plasticity and function of postsynaptic sites of neuromuscular junctions, analogous to mAbp1 and drebrin, which are known as essential players in both neurological [43][44][45]28 and immunological 30,29 synapses. In addition, DBN-1 may be involved in vesicle transport, similar to yeast and mammalian Abp1 homologues, which are well-described key regulators of receptor-mediated endocytosis, vesicle trafficking and endocytic structure disassembly [46][47][48][49]32 .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis suggested involvement of the core clathrin, actin, and dynamin modules in the majority of scission events since all coat components (clathrin, AP2, epsin2, FCHo, CALM, and NECAP) and both Hip1R (which binds clathrin and F-actin [44]) and Abp1 (which binds dynamin, F-actin, and Arp2/3 [66]) were detected at .90% of scission events, and dynamin1/2, synaptojanin2b1, myosin6, and Eps15 were detected at .75% of events. These findings agree with the widely accepted view that TfR internalizes via a clathrin-and dynamin-dependent pathway [67,68] and are in agreement with earlier studies that demonstrated an important, though nonessential, role for actin in CME in fibroblasts ( [9][10][11], but see [23]).…”
Section: The Same Core Machinery Of Cme Operates At Different Dynamicmentioning
confidence: 99%
“…Dynamin is an integral component of F-actin comets (Lee and DeCamilli, 2002;Orth et al, 2002;Schafer et al, 2002); and it is found to organize F-actin assembly in lamellipodia (Schafer, 2002, for review). Dynamin interacts with proteins like syndapin, cortactin, Abp-1, etc., to initiate Factin assembly at different intracellular sties (McNiven et al, 2000;Kessels et al, 2001;Taunton et al, 2000;;Krueger et al, 2003) and this regulates the membrane remodeling in lamellipodia, podosomes, and membrane ruffles.…”
Section: Dlc1 Regulates Dynamin-mediated F-actin Assembly At the Invementioning
confidence: 99%
“…It is shown to interact with syndapin, cortactin, Abp-1, etc., and initiate F-actin assembly at these sites (McNiven et al, 2000;Kessels et al, 2001;Taunton et al, 2000;Krueger et al, 2003). In spite of all these studies, the mechanism underlying the regulation of dynamin dependent F-actin assembly in these events is still unknown.…”
Section: Introductionmentioning
confidence: 99%